1999
DOI: 10.1046/j.1440-1827.1999.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the breast: A multifaceted study with special reference to histogenesis and neuroendocrine differentiation

Abstract: Although mucinous carcinoma (MC) of the breast is considered to originate from ductal carcinoma, it is not known whether mucinous growth begins in the intraductal carcinoma or later in the invasive carcinoma. In this study, 33 MC (16 pure without any ductal components, 10 mixed Type I with an intraductal component, seven mixed Type II with a common invasive ductal carcinoma (IDC) component)) were examined to clarify the time when mucinous growth begins. Histochemical and immunohistochemical examinations of muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In our series, MUC1 was expressed in the majority of breast cancer cases using two different antibodies; one directed against the carbohydrate side chain (MUC1) and the other directed against the apomucin protein backbone (MUC1-core). This is in concordance with previous studies using different antibodies directed against tandem repeat peptides, 11 carbohydrate side chain 41 of the extracellular domain or against the cytoplasmic domain. 42 We found associations between MUC1 expression and tumour grade and ER status where such relationships have previously been reported indicating high correlation between MUC1 expression and functional differentiation of the tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“…In our series, MUC1 was expressed in the majority of breast cancer cases using two different antibodies; one directed against the carbohydrate side chain (MUC1) and the other directed against the apomucin protein backbone (MUC1-core). This is in concordance with previous studies using different antibodies directed against tandem repeat peptides, 11 carbohydrate side chain 41 of the extracellular domain or against the cytoplasmic domain. 42 We found associations between MUC1 expression and tumour grade and ER status where such relationships have previously been reported indicating high correlation between MUC1 expression and functional differentiation of the tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, there are a few large series analyzing this phenomenon in mucinous carcinoma, and many authors concluded that there was no difference between mucinous carcinoma with or without neuroendocrine differentiation in terms of predictive value, growth patterns, and estrogen receptor status, 5,7 while another recent series did not analyze these prognostic parameters. 8 The expression of neuroendocrine markers is not unique to mucinous carcinoma of the breast. This phenomenon has been described in other breast carcinomas, including ductal carcinoma in situ (termed endocrine ductal carcinoma in situ, 9 ); the small-cell undifferentiated carcinoma that resembles small-cell carcinoma or Merkel cell carcinoma; infiltrating lobular carcinoma; and low-grade insular ductal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The significance of neuroendocrine differentiation in mucinous carcinoma has been controversial, with some authors reporting a difference in patients' age and prognosis, 4,6 while other authors concluded that no difference existed. 5,7,8 In this study, we further evaluated the clinicopathological differences between pure mucinous carcinoma with or without neuroendocrine differentiation.…”
mentioning
confidence: 99%
“…In fact, it is well known that some mucinous carcinomas of the breast are associated with neuroendocrine differentiation. [10][11][12] The tumor cells are often of low nuclear grade, with relatively little mitotic activity. The nuclear and cytoplasmic features of the tumor cells resemble those of low grade neuroendocrine tumors occurring in other organ systems.…”
Section: Discussionmentioning
confidence: 99%